Large reduction in opioid prescribing by a multipronged behavioral intervention after major urologic surgery. Issue 2 (1st October 2020) - Jacobs, Bruce L.; Rogers, Devin; Yabes, Jonathan G.; Bandari, Jathin; Ayyash, Omar M.; Maganty, Avinash; Armann, Kody M.; Worku, Hermoon A.; Pace, Natalie M.; Shah, Anup; Pekala, Kelly R.; Yu, Michelle; et al.
Abstract : Background: Surgeons play a pivotal role in combating the opioid crisis that currently grips the United States. Changing surgeon behavior is difficult, and the degree to which behavioral science can steer surgeons toward decreased opioid prescribing is unclear. Methods: This was a single‐institution, single‐arm, pre‐ and postintervention study examining the prescribing of opioids by urologists for adult patients undergoing prostatectomy or nephrectomy. The primary outcome was the quantity of opioids prescribed in oral morphine equivalents (OMEs) after hospital discharge. The primary exposure was a multipronged behavioral intervention designed to decrease opioid prescribing. The intervention had 3 components: 1) formal education, 2) individual audit feedback, and 3) peer comparison performance feedback. There were 3 phases to the study: a pre‐intervention phase, an intervention phase, and a washout phase. Results: Three hundred eighty‐two patients underwent prostatectomy, and 306 patients underwent nephrectomy. The median OMEs decreased from 195 to 19 in the prostatectomy patients and from 200 to 0 in the nephrectomy patients ( P < .05 for both). The median OMEs prescribed did not increase during the washout phase. Prostatectomy patients discharged with opioids had higher levels of anxiety than patients discharged without opioids ( P < .05). Otherwise, prostatectomy and nephrectomy patients discharged with and without opioids did not differ in their perception of postoperative pain management, activity levels, psychiatric symptoms, or somatic symptoms ( P > .05 for all). Conclusions: Implementing a multipronged behavioral intervention significantly reduced opioid prescribing for patients undergoing prostatectomy or nephrectomy without compromising patient‐reported outcomes. Abstract : Surgeons can play a pivotal role in combating the opioid crisis. This single‐institution, single‐arm, pre‐ and postintervention study shows a significant decrease in the median oral morphine equivalents prescribed after prostatectomies (from 195 to 19) and after nephrectomies (from 200 to 0) without compromises in patient‐reported outcomes after the implementation of a multipronged behavioral intervention.